A problem in information retrieval with fuzzy sets - Buell, Duncan A. (Journal of the American Society for Information Science, 1985)
The introduction of fuzzy subset concepts in document retrieval has led to a search for a system of weighted fuzzy queries in which the weights would correspond to the relative importance of each term to the entire query. The crucial step is to link mathematically the fuzzy membership function with the weight to form a retrieval status value (RSV). Buell and Kraft (1981) showed that these relevance weights cannot be used with a system of Boolean queries, and Kantor (1981) suggested a logic of weighted queries, but the most common use of NOT presents a problem. A symmetry of about one-half could be artificially introduced by shifting the range of all positive membership functions, thus imposing a certain structure on the conceptual retrieval system. This would be much closer to what is needed than previous suggestions, but the benefits and problems involved in keeping or losing various axioms of Boolean structures must be studied closely.